Metal–Organic Framework Templated Pd@PdO–Co3O4 Nanocubes as an Efficient Bifunctional Oxygen Electrocatalyst - Li, Hong‐Chao; Zhang, Ying‐Jie; Hu, Xiao; Liu, Wu‐Jun; Chen, Jie‐Jie; Yu, Han‐Qing (Advanced energy materials, 2018)
The development of high‐efficiency bifunctional electrocatalyst for oxygen reduction and evolution reactions (ORR/OER) is critical for rechargeable metal–air batteries, a typical electrochemical energy storage and conversion technology. This work reports a general approach for the synthesis of Pd@PdO–Co3O4 nanocubes using the zeolite‐type metal–organic framework (MOF) as a template. The as‐synthesized materials exhibit a high electrocatalytic activity toward OER and ORR, which is comparable to those of commercial RuO2 and Pt/C electrocatalysts, while its cycle performance and stability are much higher than those of commercial RuO2 and Pt/C electrocatalysts. Various physicochemical characterizations and density functional theory calculations indicate that the favorable electrochemical performance of the Pd@PdO–Co3O4 nanocubes is mainly attributed to the synergistic effect between PdO and the robust hollow structure composed of interconnected crystalline Co3O4 nanocubes. This work establishes an efficient approach for the controlled design and synthesis of MOF‐templated hybrid nanomaterials, and provides a great potential for developing high‐performance electrocatalysts in energy storage and conversion. This work reports a general approach to synthesize Pd@PdO‐Co3O4 nanocubes using the zeolite‐type metal–organic framework (MOF) as a template. The as‐synthesized material exhibits a high electrocatalytic activity toward Oxygen evolution and reduction reactions (OER and ORR). Synergistic effects between PdO and the robust hollow structure crystalline Co3O4 nanocubes are the main contributions to the catalyst's excellent performance.